Cell differentiation within a yeast colony: metabolic and regulatory parallels with a tumor-affected organism - Cáp, Michal; Stěpánek, Luděk; Harant, Karel; Váchová, Libuše; Palková, Zdena (Molecular cell, 2012)
Nutrient sensing and metabolic reprogramming are crucial for metazoan cell aging and tumor growth. Here, we identify metabolic and regulatory parallels between a layered, multicellular yeast colony and a tumor-affected organism. During development, a yeast colony stratifies into U and L cells occupying the upper and lower colony regions, respectively. U cells activate a unique metabolism controlled by the glutamine-induced TOR pathway, amino acid-sensing systems (SPS and Gcn4p) and signaling from mitochondria with lowered respiration. These systems jointly modulate U cell physiology, which adapts to nutrient limitations and utilize the nutrients released from L cells. Stress-resistant U cells share metabolic pathways and other similar characteristics with tumor cells, including the ability to proliferate. L cells behave similarly to stressed and starving cells, which activate degradative mechanisms to provide nutrients to U cells. Our data suggest a nutrient flow between both cell types, resembling the Cori cycle and glutamine-NH(4)(+) shuttle between tumor and healthy metazoan cells.
Keywords: geny hub; aminokyseliny; Saccharomyces cerevisiae Proteins; transkriptom; autofagie; Neoplasms; Saccharomyces cerevisiae; signální transdukce; Transcriptome; transportní systémy aminokyselin; buněčné dělení; genový knockout; Models, Biological; Signal Transduction; Stress, Physiological; kvartérní amoniové sloučeniny; spotřeba kyslíku; Genes, Fungal; Amino Acid Transport Systems; Oxygen Consumption; Animals; Autophagy; lidé; Cell Division; biologické modely; Gene Knockout Techniques; Quaternary Ammonium Compounds; Humans; zvířata; metabolické sítě a dráhy; Saccharomyces cerevisiae - proteiny; nádory; fyziologický stres; Metabolic Networks and Pathways; Amino Acids